2010
DOI: 10.1053/j.gastro.2010.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation in Hereditary Nonpolyposis Colorectal Cancer Without Mismatch Repair Deficiency

Abstract: Background & Aims-Approximately half of the families that fulfill Amsterdam criteria for Lynch syndrome or hereditary non-polyposis colorectal cancer (HNPCC) do not have evidence of the germline mismatch repair (MMR) gene mutations that define this syndrome and result in microsatellite instability. The carcinogenic pathways and the best diagnostic approaches to detect microsatellite stable (MSS) HNPCC tumors are unclear. We investigated the contribution of epigenetic alterations to development of MSS HNPCC tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 39 publications
4
77
1
1
Order By: Relevance
“…49,51,[53][54][55][56] Global DNA hypomethylation has been associated with poor prognosis, shorter survival, younger age of onset, and familial colorectal cancer risk. 39,51,[55][56][57][58][59] The predisposition to LINE-1 hypomethylation in FCCTX tumors gives an evidence for a link between distinct molecular signatures and phenotypes associated with specific epigenotypes. 59 In hereditary colorectal cancer, relatively less is known about the patterns of specific histone modifications that also regulate gene expression through controlling chromatin conformation.…”
mentioning
confidence: 99%
“…49,51,[53][54][55][56] Global DNA hypomethylation has been associated with poor prognosis, shorter survival, younger age of onset, and familial colorectal cancer risk. 39,51,[55][56][57][58][59] The predisposition to LINE-1 hypomethylation in FCCTX tumors gives an evidence for a link between distinct molecular signatures and phenotypes associated with specific epigenotypes. 59 In hereditary colorectal cancer, relatively less is known about the patterns of specific histone modifications that also regulate gene expression through controlling chromatin conformation.…”
mentioning
confidence: 99%
“…The importance of hypomethylation in this region has been highlighted in various types of human cancer, including HCC, chronic myeloid leukemia, bladder cancer, gastrointestinal stromal tumors, gastric cancer and ovarian cancer (12). Transcription of L1 induced by hypomethylation significantly correlates with the degree of malignancy, particularly in colorectal cancer (21)(22)(23). This suggests that L1 hypomethylation may serve a more important role in human cancer than the hypomethylation-induced inhibition of transcription of specific tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 82%
“…91,92 More specifically, colorectal cancers with microsatellite stable (ie, lacking mismatch-repair deficiency) and Amsterdam Criteria positive were found to display a significantly lower degree of long interspersed element-1 methylation as compared with other patient groups, ie, Lynch syndrome with identified mismatch-repair mutations and sporadic colorectal cancers with or without microsatellite instability. Long interspersed element-1 comprises a substantial portion of the human genome and its methylation correlates with global methylation status.…”
Section: Familial Colorectal Cancer Type X Is Distinct From Lynch Synmentioning
confidence: 99%
“…Genomewide DNA hypomethylation has an important role in genomic instability and carcinogenesis. 91 Additionally, it was suggested that cancers characterized by long interspersed element-1 extreme hypomethylation constitute a previously unrecognized and distinct subtype of colorectal cancer. 92 In addition to young onset (consistent with familial predisposition), colorectal cancers characterized by long interspersed element-1 hypomethylation consistently exhibited a poor prognosis.…”
Section: Familial Colorectal Cancer Type X Is Distinct From Lynch Synmentioning
confidence: 99%